P0946OXIDATIVE STRESS AND HEME METABOLISM IN RED BLOOD CELLS FROM HEMODIALYSIS PATIENTS. (6th June 2020) - Ferreira Dias, Gabriela; Bohnen, Gabriela; Grobe, Nadja; Tao, Xia; Pecoits-Filho, Roberto; Kotanko, Peter; Moreno-Amaral, Andrea N
Abstract: Background and Aims: We have previously described that indoxyl sulfate promotes red blood cells (RBC) ROS generation through organic anion transporter 2 as well as NADPH oxidase activity-dependent and GSH-independent mechanisms (Dias et al., 2018). However, there is little information regarding pathways of antioxidant balance to protect RBC from extensive oxidative stress that occurs during hemodialysis (HD). Intracellular free heme is degraded by Heme Oxygenase 1 (HO-1), which is regarded as the major cytoprotective enzyme (Maines, 1988; Gozzelino et al., 2010). In the current study, we assessed HO-1 activity and ROS production in RBC from healthy subjects and hemodialysis (HD) patients before and after HD. Method: Blood was drawn from 6 healthy individuals (CON-RBC) and 6 HD patients (HD-RBC) before (pre/HD-RBC) and after high flux HD (post/HD-RBC). Isolated RBC were stained with DCFH-DA (Abcam) for ROS measurements. To quantify HO-1, RBC were incubated with anti-HO-1 antibody (Abcam) and m-IgGκ BP-CFL 488 (Santa Cruz Biotechnology) as a secondary antibody. Samples were analyzed by flow cytometry. Results: Our results show a 4-fold increase in ROS levels in pre/HD-RBC compared to CON-RBC. ROS levels were even further increased by 1.65-fold after HD treatment in post/HD-RBC (Figure 1). Both pre/HD-RBC and post/HD-RBC showed a similarly significant increase of 3.3-fold in HO-1 compared to CON-RBC. (Figure 1). Conclusion: High levels of HO-1 may represent a defense against oxidative stress that occurs in ESKD and particularly during the HD session. Further research is needed to evaluate whether HO-1 overexpression could accelerate heme degradation and contribute to renal anemia.